2022
DOI: 10.1186/s12889-022-13591-1
|View full text |Cite
|
Sign up to set email alerts
|

Community gardens and their effects on diet, health, psychosocial and community outcomes: a systematic review

Abstract: Background We systematically reviewed the effects of community gardens on physical and psychosocial health, health behaviors and community outcomes. Methods Quantitative studies that examined associations of health, psychosocial or community outcomes with community gardens were included in the review. Studies up to December 2020 were captured from searches of Medline, Web of Science, PsycInfo, EBSCOHost and CAB Abstracts. Data were extracted and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 86 publications
1
27
0
Order By: Relevance
“…44 Similarly, mental health outcomes were mixed with evidence of reduced 44 and increased stress; 52 and both increased quality of life 52 and reduced satisfaction in life post intervention. 48 Previous research in general population samples has also revealed mixed results for community gardening interventions on health outcomes, 89 although therapeutic horticultural interventions on the whole have been observed to have positive impact on both physical and mental health. 33,90 This review also identified economic benefits of home and community gardening interventions with a significant increase in quantities of produce yielded 54 and marketing of produce.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…44 Similarly, mental health outcomes were mixed with evidence of reduced 44 and increased stress; 52 and both increased quality of life 52 and reduced satisfaction in life post intervention. 48 Previous research in general population samples has also revealed mixed results for community gardening interventions on health outcomes, 89 although therapeutic horticultural interventions on the whole have been observed to have positive impact on both physical and mental health. 33,90 This review also identified economic benefits of home and community gardening interventions with a significant increase in quantities of produce yielded 54 and marketing of produce.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…These reviews captured four hundred and forty-four studies in twenty-six countries which reflected a strong growing global interest in gardening as a public health intervention. The reviews targeted cardiovascular [ 44 ], chronic illnesses [ 23 , 45 , 46 , 47 , 48 ] and related risk factors [ 21 , 23 , 24 , 25 , 26 , 33 , 44 , 45 , 48 , 49 , 50 ]. Four reviews focused on school gardening studies [ 22 , 25 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The existing body of research on gardening interventions suggests that several challenges affect implementation and sustainability. Inadequate soil quality, water scarcity, access to/affordability of resources, availability of land, poor market linkages, lack of gardening knowledge, time constraints, high staff turnover, lack of support, labor burden and crop destruction by animals have been cited [ 21 , 22 ].There is inadequate mention of community garden interventions for Indigenous populations in published reviews [ 23 , 24 , 25 , 26 ] One review showed a positive impact on health and well-being for other vulnerable populations, including ethnic minorities and refugees, socioeconomically disadvantaged neighborhoods or low-income or food-insecure families [ 24 ]. No known existing or ongoing reviews of community gardening interventions in Indigenous populations were found through searches of MEDLINE, PROSPERO, COCHRANE or Joanna Briggs Institute (JBI) Evidence Synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the Tuvalu Department of Agriculture has advocated for the concept of a "home garden" ("fatoaga ite fale" in Tuvaluan), encouraging Tuvaluans to grow vegetables near their houses, which requires adequate space near the house, care for the crops, and continuous garden maintenance. The attributed benefits of home gardening are well-established in the literature [7,8]. Among Pacific Islands countries, home gardens have the additional potential to promote agricultural diversification and maximize self-sufficiency [9].…”
Section: Efforts In Improving Food Security In Tuvalumentioning
confidence: 99%
“…Among Pacific Islands countries, home gardens have the additional potential to promote agricultural diversification and maximize self-sufficiency [9]. Besides increasing the availability of fresh fruits and vegetables, home gardens keep people physically active and decrease stress [7].…”
Section: Efforts In Improving Food Security In Tuvalumentioning
confidence: 99%